LncRNA DARS-AS1 aggravates the growth and metastasis of hepatocellular carcinoma via regulating the miR-3200-5p-Cytoskeleton associated protein 2 (CKAP2) axis. Issue 1 (1st January 2021) - Feng, Yanqing; Wei, Gang; Zhang, Linfei; Zhou, Huadong; Wang, Wei; Guo, Peng; Cheng, Caitao; Ji, Lei; Cai, Qinghe; Feng, Yong; Tu, Huahua
ABSTRACT: Accumulating signs have found that long noncoding RNAs (lncRNAs) contribute to hepatocellular carcinoma (HCC). Here, we probed the effect and mechanism of lncRNA DARS-AS1 in HCC. The profiles of DARS-AS1 and Cytoskeleton associated protein 2 (CKAP2) in 50 HCC tissues and non-tumor tissues were examined by real-time quantitative polymerase chain reaction (RT-qPCR). DARS-AS1 and CKAP2 overexpression and/or knockdown cell models were established. The proliferation, apoptosis, invasion and epithelial-mesenchymal transition (EMT) were determined. CKAP2, and focal adhesion kinase (FAK)-extracellular signal-regulated kinase (ERK) was tested by Western blot (WB). The relationship between DARS-AS1 and CKAP2 was predicted by Bioinformatics, and the dual-luciferase reporter assay was applied to verify the targeting association between miR-3200-5p and DARS-AS1 and CKAP2. DARS-AS1 was overexpressed in HCC tissues (vs. that in non-tumor tissues) and was closely correlated with the patients' tumor stage. DARS-AS1 facilitated HCC cell proliferation and hampered apoptosis. HCC cell migration and EMT were enhanced by DARS-AS1. DARS-AS1 up-regulated CKAP2, which aggravated HCC. Further investigation illustrated that either DARS-AS1 or CKAP2 activated FAK-ERK pathway, and miR-3200-5p was competitively restrained by DARS-AS1. miR-3200-5p exerted tumor-suppressive effects in HCC and inactivated CKAP2 and FAK-ERK pathway. All in all, this study corroborates that DARS-AS1 facilitates HCC proliferation and metastasis by regulating miR-3200-5p-mediated CKAP2, which provides a potential target for HCC diagnosis and treatment. Abbreviations: CCK-8: cell counting kit-8; CKAP2: Cytoskeleton associated protein 2; cDNA:complementary DNA; DAPI: 4ʹ, 6-diamidino-2-phenylindole; DARS-AS1: DARS1 antisense RNA 1; DEPC: diethyl pyrocarbonate; DMEM-F12: Dulbecco's minimal essential medium/Ham's-F12; EMT: epithelial-mesenchymal transition; ERK: extracellular signal-regulated kinase; FAK: focal adhesion kinase; FBS: fetal bovine serum; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; HCC: hepatocellular carcinoma; HE: hematoxylin-eosin; IHC: Immunohistochemistry; LIHC: Liver hepatocellular carcinoma; lncRNAs: long noncoding RNAs; MIAT: lncRNA myocardial infarction-related transcripts; MT: Mutant; NC: negative control; PBS: phosphate-buffered saline; PMSF: Phenylmethylsulfonyl fluoride; PVDF: polyvinylidene difluoride; RT: room temperature; RT-qPCR: real-time quantitative polymerase chain reaction; SDS-PAGE: sodium dodecyl sulfate-polyacrylamide gel electrophoresis; SPF: specific pathogen-free; TMAP: tumor-associated microtubule-associated protein; TUNEL: TdT-mediated dUTP nick end labeling; V: volume; WT: wild type.